Efektivitas Pembelajaran Tatap Muka (PTM) Pasca Pandemi Di Sekolah Menengah Pertama Kota Palangka Raya - Gunarjo Suryanto Budi; Theo Jhoni Hartanto; Marcel Tri Maruto; Yemima Yemima; Muhammad Risqi (Jurnal Ilmiah Kanderang Tingang, 2022)
This study aims to determine the effectiveness of post-pandemic face-to-face learning on science subjects in the new normal era based on learning outcomes and student attendance from four Junior High Schools (SMP) in the city of Palangka Raya. This research was conducted using a quantitative approach with a survey method. Quantitative research is research where the researcher is placed as a key instrument, data collection techniques are combined and data analysis is inductive. This research was conducted in four stages, namely: 1) research preparation stage, 2) research implementation stage, 3) data analysis stage, and 4) conclusion drawing stage. This study shows that post-pandemic face-to-face learning is effective. This is based on the percentage of student attendance which shows the level of student enthusiasm in participating in face-to-face learning after the pandemic is quite high with a percentage value of 80% to 100%. In addition, student learning outcomes also increased from before the implementation of face-to-face learning (online learning) and after the implementation of face-to-face learning after the pandemic, from an average value of 78.76 increased to 80.91 after the implementation of face-to-face learning. In addition, the percentage of students who scored above the KKM score (75) also increased from 77.5% to 86.25%.